NATO Command System and Air Policing in the Polish Airspace - Krawczyk Jacek; Tomaszycki Marek (2021)
The article presents the NATO command structure with particular emphasis on the units responsible for command and control in the Polish airspace. The structure was described at three levels of command: strategic, operational and the tactical level. Moreover, the article also presents the issues concerning sovereignty in the space of the Republic of Poland and the cooperation of civil and military services in relation to the aircraft, which in an unauthorised manner crossed the state air border.